Pengaruh Chest Therapy Terhadap Penurunan Respiratory Rate Pada Balita Dengan Bronkitis Di RS Triharsi Surakarta - Putri, Ajeng Puspitasari; , Dwi Rosella K, S.St FT., M.Fis; , Yulisna Mutia Sari, SSt. FT., MSc (GRS) (2016)
Background: Bronchitis according to the American Academy of Pediatrics (2005) is a common disease in communities marked by an inflammation of the bronchial tract. Acute bronchitis is most often strikes children under 5 years old. Second, chronic bronchitis is an infection of the bronchi that lasts at least three months in the year and repeated the following year. Chronic bronchitis is more common in adults over the age of 50 years. Physiotherapy has a role in helping symptoms of bronchitis by giving chest therapy. Objective: This study aimed to determine the effect of chest therapy to decrease respiratory rate against bronchitis in infants with RS Triharsi Surakarta. Methods: The study was conducted with a quantitative approach kind of quasi experiment, with the approach of pre and post test design group to determine the effect of chest therapy to decrease respiratory rate against bronchitis in infants with RS Triharsi Surakarta. Samples of 20 people were taken through Convenience sampling method, measurements of respiratory rate in a study using a test. Results: From the results of the comparative test to get the Wilcoxon test p <0.05, indicating the influence of therapy against respiratory rate chest against bronchitis in infants with RS Triharsi Surakarta. Conclusion: There is the effect of chest therapy to decrease respiratory rate against bronchitis in infants with RS Triharsi Surakarta.